2016
DOI: 10.1179/1743281215y.0000000050
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation on novel blast furnace operation of combining coke oven gas injection with hot burden charging

Abstract: A novel blast furnace operation of coke oven gas (COG) injection simultaneously with hot burden charging has been proposed to solve the problem of insufficient heat in the BF shaft zone under the condition of COG injection and make full use of the abundant sensible heat of high temperature burden. In this paper, the novel process has been simulated with a multifluid blast furnace model. The results show that, in comparison with the operation of COG injection only, under the operation of COG injection together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The coke rate, however, can be reduced with the increased RCOG injection rate, which has also been reported in the previous research studies. 4,26,27,30,31 This is because, first, the additional thermal energy brought by the RCOG can help decrease the amount of coke to provide heat, and second, the reducing agents in RCOG, particularly hydrogen can partly replace the coke as the reactant to participate in the chemical reactions. Inside a BF, coke is combusted in front of the raceway to provide the gaseous reducing agent CO to participate in the reduction process of iron oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coke rate, however, can be reduced with the increased RCOG injection rate, which has also been reported in the previous research studies. 4,26,27,30,31 This is because, first, the additional thermal energy brought by the RCOG can help decrease the amount of coke to provide heat, and second, the reducing agents in RCOG, particularly hydrogen can partly replace the coke as the reactant to participate in the chemical reactions. Inside a BF, coke is combusted in front of the raceway to provide the gaseous reducing agent CO to participate in the reduction process of iron oxides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…29 Then, Liu et al proposed a BF novel operation, which combines the tuyere COG injection and hot burden charging to provide more thermal energy to the upper shaft. 30 The model was then applied to simulate the Mei Steel No. 2 BF with COG injection at the tuyere level.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explanation matches the results of previous studies. [49,50] In 2013, Chu and coworkers [51][52][53] conducted a 2D simulation study of the OBF process with COG injected through hearth tuyeres. Figure 5 and 6, respectively, shows the temperature distributions of solid burden and reduction degree under different oxygen contents conditions.…”
Section: Two-dimensional Modelsmentioning
confidence: 99%
“…Zhang et al examined the flow and thermochemical behaviors in an oxygen BF and found that the magnetite reserve zone wherein the composition of iron ore remains steady is significantly reduced by the strongly reducing atmosphere compared to the conventional BF. Chu and his colleagues analyzed the usage of different technologies such as top gas recycling, hot burden charging, injection of coke oven gas and natural gas, and their different combinations, which provides detailed evidence for the implementation of these technologies in aspects of the in‐furnace state and global performance.…”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%